A CONTRASTIVE ANALYSIS OF VERB IN INDONESIAN AND ENGLISH LANGUAGE ON SINDO NEWS - Pasaribu, Rebekka Viona; Siringoringo, Daniel J. O.; Nainggolan, Vivi Grasella; Sitanggang, Anita (Transpublika Publisher, 2022)
This study contrasted verb features that exist between the two languages, with Indonesian as the source language and English as the target language. The contrastive analysis is used to help second language or foreign language learners understand the target language being studied more easily. The problem limitation is focused on analyzing the differences in verbs for action and non-action verbs between English and Indonesian (https://ekbis.sindonews.com/read/824401/33/dunia-gonjang-ganjing-luhut-ekonomi-kita-salah-satu-yang-terbaik ) in SINDO News. The research used descriptive qualitative research. The technique of analyzing data used in this study is based on contrastive analysis from SINDO News. The researchers searched and found data from Google media. After that, the researcher analyzes each word from the economic news, which includes the action verb and non-action verb. Next, the researcher analyzes for words that have the same meaning in the action verb and non-action verb by using an English dictionary, then compares them with the same word in Indonesian using the Indonesian dictionary. The results of the analysis show that there are 15 verbs found in news.